Effects of monensin source on in vitro rumen fermentation characteristics and performance of Bos indicus beef bulls offered a high-concentrate diet. Issue 1 (1st October 2019) - Teixeira, Daniel A A; Cappellozza, Bruno I; Fernandes, Juliano R; Nascimento, Kaique S; Bonfim, Lorena E L M; Lopes, Catarina N; Ehrhardt, Jorge A C; Peres, José R; Harris, Simon A; Simas, José M C; Richardson, Leo F
Abstract: In Exp. 1, Brachiaria ruziziensis (11.1 % CP) was inoculated or not with two sources of monensin, resulting in three treatments: 1) no monensin inoculation (CONT), 2) 20 mg of monensin sodium-A/kg of DM (Elanco Animal Health; MON-A), and 3) 20 mg of monensin sodium-B/kg of DM (Shandong Qilu King-Phar Pharmaceutical Co. Ltd.; MON-B). Three rumen-fistulated Jersey steers were offered a cool-season forage-based diet and were used as the rumen inoculum donors. Volatile fatty acids concentrations were evaluated at 0, 6, 12, 24, 30, and 48 h after treatment inoculation. Overall, acetate and butyrate concentrations were reduced in MON-A vs. CONT ( P ≤ 0.02), whereas both monensin products reduced Ac:Pr ratio vs. CONT ( P ≤ 0.01); however, MON-A also ( P = 0.05) reduced the Ac:Pr ratio vs. MON-B. A treatment × hour interaction was detected for rumen propionate concentration ( P = 0.01), primarily because MON-A resulted in greater propionate than CONT and MON-B at 24 and 48 h ( P ≤ 0.03), but no differences were observed between CONT vs. MON-B ( P ≥ 0.27). In Exp. 2, 240 Nellore bulls (initial BW = 363.2 ± 40.9 kg) were ranked and blocked according to initial BW, and within blocks animals were allotted into pens ( n = 10 pens/treatment). Pens were randomly assigned into one of three treatments: 1) corn-based diet with no monensin (CONT), 2) CONT plus 28 mg of MON-A/kg of DM, and 3) CONT plus 28 mg of MON-B/kg of DM. The CONT diet was composed of sugarcane bagasse, ground corn, DDGS, urea, and a mineral-vitamin mix. The experimental period lasted 106 d and was divided into a 21-d adaptation period and an 85-d finishing phase. During the adaptation phase, both monensin sources increased ( P ≤ 0.01) BW change, ADG, and F:G, as well as reduced DMI variation ( P = 0.02). When the entire experimental period was evaluated, no treatment effects were detected for final BW, DMI, and ADG ( P ≥ 0.26). Nonetheless, DMI variation was reduced as monensin was included ( P = 0.01) and only MON-A improved the efficiency by reducing F:G vs. CONT ( P = 0.05) and biological efficiency vs. MON-B ( P = 0.05). Additionally, carcass ADG tended ( P = 0.10) to be greater for MON-A vs. MON-B, whereas no other differences in the carcass characteristics were observed ( P ≥ 0.53). In summary, the source of monensin inoculated in vitro and offered to Nellore bulls during the feedlot phase significantly affected the energetic efficiency and the performance of the animals.